Information balance in social media: the debate on the reform of the Colombian health system on platform X (formerly Twitter) (Sociología y tecnociencia, 2026)
This article analyzes how major media outlets in Colombia framed the health care system reform proposed by President Gustavo Petro (2022–2024) on the platform X (formerly Twitter). Using a mixed-methods approach that combines sentiment analysis and framing theory, the study examines 7,398 tweets published by ten high-reach media organizations. The results reveal a dominant pattern of neutral and negative frames, with only marginal presence of favorable narratives. This coverage—amplified by algorithmic repetition and editorial selectivity—contributed to eroding public acceptance of the reform through negative framing. Far from acting as neutral providers of information, the media functioned as political actors that shaped public perception and citizen trust. Drawing on theories of media framing, public agenda, and sociological trust, the study shows how emotionalized and polarized coverage—produced within concentrated ownership structures—undermined deliberative discourse and reinforced perceptions of political crisis. Methodologically, the research demonstrates both the potential and limitations of large language models (LLMs) in identifying affective patterns in political communication, and advocates for their complementary use alongside qualitative interpretive approaches. This article contributes to global debates on media and politics in digital environments, situating the Colombian case within a broader pattern of mediatized resistance to social reforms in Ibero-America and other regions.
Keywords: mass media; social media; social policy; health system reform; communication